Transcultural adaptation of interpersonal psychotherapy in Asia. (22nd October 2020) - Stuart, Scott; Pereira, Xavier V.; Chung, Joseph Pui‐Yin
Abstract: Interpersonal Psychotherapy (IPT) has been utilized with great efficacy and effectiveness across many cultural settings. The attachment theory upon which IPT rests provides a strong foundation for IPT cross‐culturally: regardless of their geographic location, people are people and their relationships are important. Though the structure of families and individual social roles varies greatly across cultures, people relate to one another. They become distressed when they have problems with interpersonal conflict, change, and loss of relationships. In this article, we review the basics of IPT and then describe the ways in which cultural adaptations can be made for people in Asia. Both are large tasks—to summarize IPT concisely while providing sufficient information is difficult; describing cultural adaptions for people in geographical areas from Russia to China to India to Southeast and Central Asia and all of the ethnic and language groups that area includes is nigh well impossible within a review article. Thus we have restricted our cultural overview to areas in which we have experience clinically and in which we have been active with IPT training, supervision, and implementation. All of the work we describe, however, elaborate on the principles of cultural adaptations which can be used to implement IPT in other local contexts.